2016
DOI: 10.5539/gjhs.v8n11p233
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Health Policies Designed to Control and Prevent Diabetes in Saudi Arabia

Abstract: <p>A trend analysis of the prevalence of diabetes in Saudi Arabia revealed a steep increase in diagnosis rates for the disease between the years 1989 and 2009. Between these years, the percentage of the population suffering from diabetes rose from 10.6% to 32.1% of the adult population, and the diagnosis rate is likely to increase in the future. The controlling and prevention of diabetes in the future, therefore, would potentially benefit from a scholarly review of current policies and programmes designe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…In addition, education with a cultural approach has been proven to increase knowledge, attitudes, and skills in controlling blood sugar levels in West Java, Indonesia. The same condition shows that a cultural approach is very important in the Saudi Arabian environment for improving DM treatment behavior (Alharbi et al, 2016;Badriah et al, 2021).…”
Section: Discussionmentioning
confidence: 82%
“…In addition, education with a cultural approach has been proven to increase knowledge, attitudes, and skills in controlling blood sugar levels in West Java, Indonesia. The same condition shows that a cultural approach is very important in the Saudi Arabian environment for improving DM treatment behavior (Alharbi et al, 2016;Badriah et al, 2021).…”
Section: Discussionmentioning
confidence: 82%
“…Studies were excluded if any of the following criteria were met: (1) the study focused on a type of diabetes other than T2DM (e.g., type 1 or gestational diabetes); (2) there was a specific study population, such as admitted patients or patients who had specific comorbidity; (3) the study reported only genetic, biochemical (e.g., vitamins, medication and serum), and environmental pollution (e.g., chemical and radiation) risk factors; (4) the study also excluded other types of publications, including intervention (e.g., RCT), qualitative, review, pilot studies, letters, commentaries, abstract, dissertations, and editorials; or (5) the study was published before 2006. The reason for restricting the data search to 2006 and after was to address the issue of poor glycaemic control after the country's undertook its first national strategy to prevent chronic disease in cooperation with the World Health Organization (WHO) in 2006 17 . Cross‐sectional studies that followed the ADA standards of inadequate glycaemic control, that showed HbA 1c ≥7% (53 mmol/mol) for non‐pregnant adults, or that partially followed ADA standards, but failed to report that pregnant women, were included in the quantitative data synthesis of prevalence (meta‐analysis) 11 .…”
Section: Methodsmentioning
confidence: 99%
“…In Saudi Arabia, the Ministry of Health established specialized centers for the prevention, treatment, and rehabilitation of patients with T2DM through a network of integrated facilities. Other initiatives like the National Awareness Program for Diabetes 2013, the Antidiabetes Education National Program, and the National Executive Plan of Diabetes Control (2010‐2020) are crucial for primary and secondary prevention 175,176 . Countries like Oman and the UAE have initiated screening programs that can be instrumental for the early detection of noncommunicable diseases (NCDs) 177 .…”
Section: Health System Levelmentioning
confidence: 99%
“…Other initiatives like the National Awareness Program for Diabetes 2013, the Antidiabetes Education National Program, and the National Executive Plan of Diabetes Control (2010‐2020) are crucial for primary and secondary prevention. 175 , 176 Countries like Oman and the UAE have initiated screening programs that can be instrumental for the early detection of noncommunicable diseases (NCDs). 177 On the same lines, the Egypt National Multisectoral Action Plan for Noncommunicable Diseases 2017‐2021 was formed with emphasis on the following strategic areas: governance, risk reduction, health promotion, early detection and management, surveillance, monitoring and evaluation, and research.…”
Section: Health System Levelmentioning
confidence: 99%